The Optical properties of Fe-Doped TiO2 films prepared by Hydrothermal Technique - J. Hashim, Sattar; N. Salman, Odai; I. Hasson, Khaleel (Al-Nahrain Journal of Science, 2020)
TiO2 films doped with Fe at (0.1, 0.3, 0.7, 1.5 at %) were successfully deposited on the fluorine doped tin oxide (FTO)-glass substrate using hydrothermal technique. X-Ray Diffraction (XRD) analysis showed that the only phase obtained of TiO2 is rutile. Moreover, the crystallinity did not have remarkable change after doping. Ultra violet-visible (UV-vis) spectroscopy analysis show that the energy band gap value (Eg) decreases slightly with the increase of the doping concentration from 0.1 to 0.3 at%. The reflectivity measurements in general gave identical results but with higher values of Eg. Urbach energy for doping concentrations 0.7 and 1.5 at % is quite high and in the range 1-2 eV.